2010
DOI: 10.1007/s12245-010-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undiagnosed hypoxemia in adults and children in an under-resourced district hospital in Zambia

Abstract: BackgroundIn adequately resourced clinical environments, diagnosis of hypoxemia via pulse oximetry is routine. Unfortunately, pulse oximetry is rarely utilized in under-resourced hospitals in developing countries.AimThe prevalence of undiagnosed hypoxemia among adults and children with illnesses other than pneumonia in these environments remains poorly described.MethodsThis cross-sectional analysis of the prevalence of hypoxemia was conducted in Kapiri Mposhi, Zambia, at the 60-bed District Hospital, which ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…In this study, hypoxaemia was found among many patients with a variety of diagnosis, though acute respiratory infection accounted for a majority (27.5%) of the cases, closely followed by malaria (10.0%) and diarrhoea (10.0%). This was in line with the report of Foran [20] that the most common diagnosis among the patients with hypoxaemia was respiratory infections. Acute respiratory tract infection, especially pneumonia is a very serious disease in children because it is one of the major killers of children under five years of age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, hypoxaemia was found among many patients with a variety of diagnosis, though acute respiratory infection accounted for a majority (27.5%) of the cases, closely followed by malaria (10.0%) and diarrhoea (10.0%). This was in line with the report of Foran [20] that the most common diagnosis among the patients with hypoxaemia was respiratory infections. Acute respiratory tract infection, especially pneumonia is a very serious disease in children because it is one of the major killers of children under five years of age.…”
Section: Discussionsupporting
confidence: 92%
“…This study investigated the prevalence of hypoxaemia among children with different diagnosis in the children outpatient clinic in the Department of Paediatrics, University of Port Harcourt Teaching Hospital. The overall prevalence of hypoxia in this study was 11.4%, which is slightly higher than the 8% reported by Foran [20] among patients on admission in a district hospital in Zambia, though their sample population consisted of children and adults, while ours consisted of only children. It was also higher than the 5.3% prevalence of hypoxaemia reported by McCollum among hospitalized Malawian children under 15 years of age.…”
Section: Discussioncontrasting
confidence: 73%
“…In this study, 10.36% of the total patients admitted in the hospital had hypoxia. In previous studies[458] carried out in various hospitals, 7.8% to 40% of the study subjects had hypoxia. In medical wards, the most common diagnosis among the patients of hypoxia was stroke in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There are three commonly used methods to supply ICUs in resource-limited settings with oxygen: oxygen cylinders, oxygen concentrators, and centralized, piped oxygen systems [73]. Oxygen cylinders provide pressurized oxygen at variably high flow rates but-depending on their size-only do so for a limited period.…”
Section: Oxygenmentioning
confidence: 99%
“…Multiple studies from resource-limited settings demonstrated greater cost reductions with oxygen concentrator systems compared to cylinders and generators. In Papua New Guinea, the overall 2-year cost estimate for cylinders, capable of producing 35,000 L/day, was approximately USD $205,000 when compared to three oxygen concentrators (USD $82,400) and an oxygen generator system (USD $390,000), both capable of producing 60,000 L/day, [73]. In The Gambia, annual costs for cylinders at one hospital were USD $152,747 vs. USD $18,742 for concentrators with 24 h availability of grid power [76].…”
Section: Oxygenmentioning
confidence: 99%